KAJIAN KETERSEDIAAN AIR PADA DAERAH TANGKAPAN AIR (DTA) WADUK PAMUKKULU - Hendy Adiyat Nugraha; Dyah Ari Wulandari (Racic : Rab Construction Research, 2025)
The Pamukkulu Dam is a multi-purpose dam designed to serve the irrigation water needs of the Pamukkulu Irrigation Area (D.I Pamukkulu), provide raw water supply, and control flooding. The dam has a total storage capacity of 82,57 million m3, with a dead storage volume of 4,95 million m3. Currently, the dam is in the preparation stage for reservoir operation, where water availability is a critical factor. Water availability is calculated based on the inflow discharge pattern for each condition year using the Weibull method. The inflow (water availability) is determined by transforming rainfall data into streamflow discharge using the F.J. Mock method. The inflow discharge of the reservoir is categorized into three conditions: "Dry Year": Annual inflow volume < 153,60 million m3 (probability 0–33,33%), "Normal Year": Annual inflow volume between 153,60–213,97 million m3 (probability 33,33%–66,67% "Wet Year": Annual inflow volume > 213,97 million m3 (probability 66.67%–100%). Based on the studies conducted, the total water availability (inflow) is as follows for a "Wet Year", 306,02 million m3, For a "Normal Year", 165,31 million m3, For a "Dry Year", 85,40 million m3